A Case of Legal Blindness Secondary to Optic Nerve Head Drusen - Bennett, Loren Wallace (Canadian Journal of Optometry, 2022)
Optic nerve head drusen are relatively infrequent abnormalities of the optic disc that are usually discovered as incidental findings during a routine eye examination. While typically considered to be benign, visual field loss due to the drusen is not uncommon. Visual field defects are more prevalent in superficial drusen than buried drusen, and can present as nerve fiber bundle defects, generalized concentric constriction, or enlargement of the blind spot. The extent of damage is variable, but it is rare that the degree of field loss leads to substantial functional impairment. This case presents a patient with significant bilateral concentric field loss secondary to optic nerve drusen that caused severe visual impairment and disability.